Underestimating the Relationship Between Academic Advising and Attainment: A Case Study in Practice - Holland, Claire; Westwood, Caroline; Hanif, Naveen (Frontiers in Education, 2020)
The Higher Education Academy (2015) has highlighted attainment alongside access, retention and progression as key areas of foci in order to fulfill the aspiration to provide all students with the opportunities and support required to succeed in Higher Education. Although previous research into academic advising has focused on the impact upon student satisfaction and retention, the impact upon attainment is underexplored. This research aims to explore the extent of the relationship between advising and attainment and answers the call by bodies such as Advance HE (formerly the Higher Education Academy) to recognise that academic advising is vital to student success. This research provides a contribution to the body of knowledge around academic advising, in the form of a case study undertaken to identify the impact of academic advising on student attainment at Sheffield Hallam University. A focus group and questionnaire were employed to gather data from final year undergraduate students at Sheffield Hallam University. Findings indicate that the impact of academic advising on attainment is both explicit and implicit, with support in areas beyond academic studies having a significant impact on student experiences. In addition this research also questions the perceived meanings of attainment in HE and proposes that attainment should be viewed as holistic attainment whereby students are developed as a whole, better enabling them to deal with the HE environment and beyond rather than being limited to academic numerical attainment.